Please do not recycle! Translation reinitiation in microbes and higher eukaryotes - Gunišová, Stanislava; Hronová, Vladislava; Mohammad, Mahabub Pasha; Hinnebusch, Alan G; Valášek, Leoš Shivaya (FEMS microbiology reviews, 2018)
Protein production must be strictly controlled at its beginning and end to synthesize a polypeptide that faithfully copies genetic information carried in the encoding mRNA. In contrast to viruses and prokaryotes, the majority of mRNAs in eukaryotes contain only one coding sequence, resulting in production of a single protein. There are, however, many exceptional mRNAs that either carry short open reading frames upstream of the main coding sequence (uORFs) or even contain multiple long ORFs. A wide variety of mechanisms have evolved in microbes and higher eukaryotes to prevent recycling of some or all translational components upon termination of the first translated ORF in such mRNAs and thereby enable subsequent translation of the next uORF or downstream coding sequence. These specialized reinitiation mechanisms are often regulated to couple translation of the downstream ORF to various stimuli. Here we review all known instances of both short uORF-mediated and long ORF-mediated reinitiation and present our current understanding of the underlying molecular mechanisms of these intriguing modes of translational control.
Keywords: Open Reading Frames; otevřené čtecí rámce; Bacteria; proteosyntéza; Animals; Humans; Protein Biosynthesis; lidé; zvířata; Eukaryota